2015
DOI: 10.5539/ijms.v7n5p33
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Corporate Social Responsibility, Consumer-Company Identification, Brand Prestige, and Purchase Intention

Abstract: This study analyzes relationships between corporate social responsibility, consumer-company identification, brand prestige, and purchase intention. A self-report survey yields data for 252 college students. After confirming reliability and validity of survey questionnaire, the structural equation modeling was used for tests the model. Results were summarized as follows: (a) CSR image has a significant positive effect on brand prestige and consumer-company identification. (b) Brand prestige has a significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…These items relate to intentions regarding the next purchase, purchasing in the long term and the surety of making a purchase. This scale has been used by Bigné and Currás (2008) and Chen et al (2015) with high reliability (0.81-0.91).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These items relate to intentions regarding the next purchase, purchasing in the long term and the surety of making a purchase. This scale has been used by Bigné and Currás (2008) and Chen et al (2015) with high reliability (0.81-0.91).…”
Section: Methodsmentioning
confidence: 99%
“…The literature provides solid evidence that CSR behaviour is an important factor behind consumers' purchase decision processes (Creyer and Ross, 1997). Scholars have also reported that perceived CSR strengthens consumer loyalty, which increases the likelihood of choosing the firm's products (Chen et al, 2015).…”
Section: Loyalty As An Antecedent To Purchase Intention and Corporatementioning
confidence: 99%
See 1 more Smart Citation
“…...(1) PI = β 1 BP + β 2 BF + β 3 BA + β 4 PQ + e2 ... (2) The exogen variables in this research are : 1. brand prestige which consist of high status, upscale, social status. 2.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It is supported by [3] whereas they proved that brand prestige and brand awarness have a significant influence on perceived quality and purchase intention. Other perspectives can be compared is from [2] hereas they more interested in the influenced of CSR image on Brand Prestige and consumer company identificaton and its implication on purchase intention. They proved that CSR Image has a significant influences on brand prestige, consumer company identification and purchase intention, while [13] proved that brand familiarity has a significant influences on perceived quality.…”
Section: Introductionmentioning
confidence: 99%